Project and Design Literacy as Cornerstones of Smart Education Proceedings of the 4th International Conference on Smart Learning Ecosystems and Regional Development - Rehm, Matthias; Saldien, Jelle; Manca, Stefania (Smart Innovation, Systems and Technologies, 2020)
XVI, 288 p. 62 illus., 44 illus. in color.